Refleksi Pemisahan Tahapan Pemilihan Langsung Kepala Daerah (Analisis isi Era Undang-Undang Nomor 32 Tahun 2004 dan Peraturan Pemerintah Nomor 6 Tahun 2005) - Fitri, Suci Emilia (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2015)
New local elections system (Pilkada Langsung) is basically a part of efforts to further the processtowards a democratic institution, especially for improving the quality of democracy in the region tomeet regional autonomy effective and efficient. Election driven by the emergence of the phenomenon ofpiracy authority of the people, followed by the emergence of abuse of power by legislators sebahagian theperiod 1999 - 2004, direct elections under the auspices of Law No. 32 of 2004 and GovernmentRegulation 6 Year 2005 is the door to enter the era of true democracy in Indonesia. This study isoriented to analyze the substance of the regulations.